Jet lag and air travel: implications for performance - Reilly, T.; Waterhouse, J.; Edwards, B. (Clinics in Sports Medicine, 2005)
This review focuses on travel stress in athletes. An outline of the circadian system is presented, followed by an explanation of how disturbances to its regulation are related to jet lag. There are consequences of jet lag that affect exercise performance and health. Measures to ameliorate adverse effects of jet lag include behavioral or pharmacologic strategies. Coaches and mentors and the athletes they support should be considered when preparing for long-haul flights across multiple meridians